Assessment of Nonconformity to Prescription Writing Requirements and Prescription Errors: A Community Based Study - Z, Inamdar S.; R.B, K. Rucha, Kotnal; R. V, Kulkarni; C. C, Simpi; A, Singh.; A. G, Reddy; Jagdeesh, P.; Manitheja, K.; Arun, N.; Vishal, B. (Indian Journal of Pharmacy Practice)
Background: Drug therapy may not be successful if the process of writing prescription, dispensing and administration is not appropriately performed resulting into medication errors, which are unfortunately a reality in most health care settings. Approximately 30% of problems occurring during hospitalization are related to medication errors, causing great economic impact, serious morbidity and mortality. So it was thought of interest to study non compliance with prescription writing requirements and prescription errors in a community based setting. Methodology: The study was conducted in the community pharmacies for over a period of two months. The new prescriptions were screened prospectively to assess non compliance for one or more of the legal or the procedural requirements of prescription writing and was recorded in a standard data collection form. Result: Of the 1488 prescriptions screened during the study, 98.7% had one or more of the legal or procedural requirements missing. These errors of omission are patient’s age, gender, weight, dose, frequency, course prescribed. Errors of commission involved related to dosage form 4.91% and Polypharmacy 58%. These errors occurred in considerable number regarding important variables involving all health care professionals working in patient care. Conclusion: The study shows a low compliance to the legal and procedural requirements for prescription writing and denotes significant scope to educate and emphasize the importance of writing clear and complete prescriptions to avoid medication related injuries, thus evidencing the need of constant evaluation of these events in order to prevent them and assure greater safety and success in the therapy.
Keywords: Prescription Error; Polypharmacy; Medication error; Prescription